Fungi Associated With Common Spices In Bangladesh - Sultana, Tusnim; Shamsi, Shamim; Bashar, MA (Journal of the Asiatic Society of Bangladesh, Science, 2014)
Association of fungi in chili (Capsicum fruticance L.), coriander (Coriandrum sativum L.) and turmeric (Curcuma longa L.) was investigated. A total of 19 species of fungi under ten genera and one sterile mycelial fungus was isolated from the three spices. Out of ten genera three belong to Phycomycetes, one genus belongs to Ascomycetes and rest belongs to Deuteromycetes. The most frequent contaminants of the spices were Aspergillus niger van Tieghem, A. flavus Link, Fusarium nivale, Pestalotia sp. and Rhizopus sp. Dried fruits of the spices showed maximum number of fungal association in comparison with the respective commercial brand powder samples. Out of three plant extracts. A. sativum was found to inhibit the growth of all the test isolates at all concentrations. Asiat. Soc. Bangladesh, Sci. 40(2): 179-186, December 2014